EFFECT OF A SUPPLEMENTED DIET WITH MELATONIN ON PERFORMANCE OF JAVAEN BARB Systomus orphoides (Valenciennes, 1842) JUVENILE - Radona, Deni; Sudrajat, Agus Oman; Alimuddin, Alimuddin; Manalu, Wasmen; Carman, Odang; Dewi, Raden Roro Sri Pudji Sinarni (Agency for Marine and Fisheries Extension and Human Resources, 2023)
Javaen barb is a native fish in Indonesian inland water with economic value and the potential to be developed as cultured fish resources and ornamental commodities. In the development of aquaculture, there are still problems, such as the low adaptability of the larvae, so that their survival is also low. This study was conducted to evaluate the effect of melatonin supplementation on the productivity of Javaen barb fish juveniles in culture containers. This study was conducted experimentally using a completely randomized design consisting of four treatments with different doses of melatonin supplementation, i.e., A) control (without melatonin supplementation), B) 0.2 mg/100 g of feed, C) 0.4 mg/100 g feed, and D) 0.6 mg/100 g feed, each treatment was repeated three times. Javaen barb juveniles were kept in an aquarium measuring 30×36×60 cm with a water level of 40 cm, consisting of 12 units. Each aquarium was stocked with 150 individuals and given an aeration system with the same air pressure intensity. Feeding was carried out ad-libitum with a frequency of three times daily for 180 days of rearing. The results showed that melatonin supplementation of as much as 0.6 mg/100 g of feed was able to increase the growth of Javaen barb fish juvenile with the highest survival rate (81.33 ± 0.54 %) and feed conversion ratio (2.61 ± 0.14). Melatonin supplementation of 0.6 mg/100 g of feed had higher total leukocyte (3.41±0.73×104 cells/mm3) and hemoglobin (5.07±0.12 g%) values and provided the best production performance in Javaen barb juveniles.